Educational Psychology and Learning: Does Mental Abilities and Self-regulated Learning Influence Learning Performance: A Survey Study on Vietnamese Educational Institutions - Le Thi Ngoc Diep, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Uncertain environmental conditions that impact children's cognitive abilities and self-learning capacities have created a number of challenges for student education today. These challenges require the attention of the researchers. Consequently, this paper investigates the influence of cognitive talents and self-regulated learning on students' academic performance in Vietnamese educational institutions. This study also examines the moderating effect of educational psychology on the relationships between mental abilities, self-regulated learning, and learning performance in Vietnamese educational institutions. The article collected primary data from chosen students via questionnaires. In addition to employing the smart-PLS statistical technique to analyze the reliability and validity of the questions and variables, the study also tested its hypotheses. The results suggested that cognitive ability and self-regulated learning favorably influence academic success. The data also demonstrated that educational psychology strongly moderates the relationship between mental talents, self-regulated learning, and students' academic achievement in Vietnamese educational institutions. The article aids in developing regulations for increasing student performance by enhancing their cognitive and learning capacities.